GeoGebra and ChatGPT as Support Tools to Find Particular and General Solutions in Non-homogeneous Linear Second-Order Differential Equations - Jorge Olivares; Melissa Sanchez; Alexandra Burgos; Pablo Martin (Mathematics and Computer Science: Research Updates Vol. 5, 2025)
This work focuses on the solution of non-homogeneous linear differential equations of second order, using technological tools such as GeoGebra and ChatGPT. These tools are especially useful in the context of the differential equations course for mathematics pedagogy students at the Universidad de Antofagasta, Chile. The use of GeoGebra, a free software, has grown in the teaching of mathematics, since it allows students to better visualise and understand mathematical concepts. On the other hand, artificial intelligence, ChatGPT, has proven to be a valuable resource in learning, providing explanations and examples that facilitate the understanding of the topics. The combination of both technological resources not only improves the learning experience but also enhances the teaching of mathematics, making students more motivated and engaged. In conclusion, this innovation in the teaching of differential equations seeks not only to solve calculations but also to foster a more dynamic and effective learning environment.